Digital Payment Quality and User Behavior in Social Commerce vs Marketplace Platforms: Evidence from TikTok Shop and Indonesian E-Commerce - Alinda Putri Nur Rahma; Zaenal Arifin (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2026)
This study investigates the influence of digital payment system quality on consumer purchase behavior and sales efficiency across different e-commerce platforms in Indonesia, with a focus on TikTok Shop and established marketplaces such as Shopee and Tokopedia. The research aims to assess how payment method completeness, payment security, and payment speed affect user behavior and operational performance in digital commerce ecosystems, driven by the growing integration of social features and instant transactions in online platforms. A quantitative approach was employed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with data collected from 242 respondents, split evenly between consumers and merchants. Multi-Group Analysis (MGA) was applied to compare platform-specific effects. The findings reveal that all dimensions of digital payment quality have a significant positive impact on their respective dependent variables. Payment security is the strongest predictor of consumer purchase behavior, especially on TikTok Shop, while payment method completeness exerts greater influence on traditional marketplaces. On the seller side, payment speed enhances sales efficiency most significantly on TikTok Shop, reflecting the platform’s reliance on fast-paced viral commerce. The study contributes to theoretical frameworks by demonstrating the varied relevance of TAM and TPB constructs in different platform contexts. It offers practical insights for platform developers and merchants seeking to optimize payment systems to improve user trust and operational effectiveness. The study also highlights the need for further research involving broader demographics and emerging payment technologies to deepen understanding of digital transaction behaviors.